2018
DOI: 10.1186/s12890-018-0741-2
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of LPS-induced pulmonary dysfunction and its recovery occur independent of T cells

Abstract: BackgroundThe acute respiratory distress syndrome (ARDS) is a serious disease in critically ill patients that is characterized by pulmonary dysfunctions, hypoxemia and significant mortality. Patients with immunodeficiency (e.g. SCID with T and B cell deficiency) are particularly susceptible to the development of severe ARDS. However, the role of T cells on pulmonary dysfunctions in immune-competent patients with ARDS is only incompletely understood.MethodsWild-type (wt) and RAG2−/− mice (lymphocyte deficient) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 30 publications
2
19
0
Order By: Relevance
“…However, in DAD due to other aetiologies, neutrophils have been described early in the course of disease and other chronic inflammatory cells in later stages regardless of whether mechanical ventilation has been used or not. 21,[34][35][36][37][38][39] In other viral pneumonias, including influenza [40][41][42][43] and Ebola, 44 the host inflammatory response has been shown to play a distinct role in pathogenesis in addition to direct damage from viral infections. It is reasonable to hypothesise that this is also the case in severe SARS-CoV-2 infections, but more research on this question is needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in DAD due to other aetiologies, neutrophils have been described early in the course of disease and other chronic inflammatory cells in later stages regardless of whether mechanical ventilation has been used or not. 21,[34][35][36][37][38][39] In other viral pneumonias, including influenza [40][41][42][43] and Ebola, 44 the host inflammatory response has been shown to play a distinct role in pathogenesis in addition to direct damage from viral infections. It is reasonable to hypothesise that this is also the case in severe SARS-CoV-2 infections, but more research on this question is needed.…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude the possibility that the presence of these chronic inflammatory cells could be related to the longer periods of mechanical ventilation in these patients. However, in DAD due to other aetiologies, neutrophils have been described early in the course of disease and other chronic inflammatory cells in later stages regardless of whether mechanical ventilation has been used or not 21,34–39 . In other viral pneumonias, including influenza 40–43 and Ebola, 44 the host inflammatory response has been shown to play a distinct role in pathogenesis in addition to direct damage from viral infections.…”
Section: Discussionmentioning
confidence: 99%
“…However, 3 hr after LPS exposure, Mch (10-300 mg/ml) challenge induced significantly higher increases in lung resistance than PBS exposure alone. By 6 and 24 hr post-LPS exposure, these effects on lung function returned to near baseline levels, and no significant differences relative to the PBS controls were apparent (Verjans et al, 2018). In this study, we demonstrated that compared with the control treatment, MCTR1 treatment improves the survival rate of septic mice.…”
Section: Discussionmentioning
confidence: 53%
“…In the 2nd phase, the host's immune response is partially deregulated, resulting in an imbalance between pro-inflammatory and anti-inflammatory cytokine responses that ultimately leads to life-threatening tissue damage, multiple organ failure, and vascular dysfunction and death. Sepsis is frequently associated with ARDS characterized by severe respiratory failure with reduced pulmonary functioning and increased oxidative stress (5). As sepsis progresses the heart starts beating rapidly and breathing becomes rapid as a compensatory mechanism in the initial stage but followed by a drop in blood pressure (6), resulting from reduced oxygen supply to vital organs like the brain, heart, lungs and kidney leading to multiple organ failure (7).…”
Section: Introductionmentioning
confidence: 99%